2017
DOI: 10.1111/apa.14059
|View full text |Cite
|
Sign up to set email alerts
|

Elective transfers of preterm neonates to regional centres on non‐invasive respiratory support is cost effective and increases tertiary care bed capacity

Abstract: The elective transfer of stable neonates on NCPAP from level three to level two NICUs within an established clinical network led to substantial cost savings, was safe and increased the bed capacity at the two level three NICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…Three of 858 patients (0.4%) required escalation of the mode of ventilation during transport ( 15 ). Five additional studies in our review demonstrated the safety of NIV in lengthy ground and air transport, in rural settings, and for preterm neonates outside the hospital setting ( 16 , 20 , 23 , 26 , 29 ). In one study, none of 118 pediatric patients on NIV during transport required intubation, despite a mean transport time of 163 min ( 20 ).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Three of 858 patients (0.4%) required escalation of the mode of ventilation during transport ( 15 ). Five additional studies in our review demonstrated the safety of NIV in lengthy ground and air transport, in rural settings, and for preterm neonates outside the hospital setting ( 16 , 20 , 23 , 26 , 29 ). In one study, none of 118 pediatric patients on NIV during transport required intubation, despite a mean transport time of 163 min ( 20 ).…”
Section: Resultsmentioning
confidence: 83%
“…Two studies conducted in remote settings suggested that nCPAP and nHFT are safe in air transport ( 23 , 26 ). Another study reported no adverse events in the interfacility transfer of 99 preterm neonates on nCPAP and concluded that this practice was both safe and cost-effective ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zein et al. report that transferring infants between level three and level two neonatal intensive care units (NICU) in Calgary, Canada, was safe and resulted in cost savings of 2.65 million Canadian dollars during the two‐year study period. It also freed up 848 level three NICU days for potentially sick neonates.…”
Section: Optimising the Cost Savings And Clinical Outcomes Of Neonatamentioning
confidence: 99%